2016
DOI: 10.17844/jphpi.v19i3.14541
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Microbiological Characteristics of Ronto During Storage

Abstract: The purpose of this study was to determine the physical, chemical, and microbiological changes of ronto during storage at room and cold temperatures. Ronto was prepared by mixing fresh shrimp, salt, and rice with a ratio of 7 : 1 : 2 and fermented in a closed container for 14 days. Ronto produced was stored at room and cold (5o C) temperatures. Samples were withdrawn every 4 weeks and analyzed for its physical, chemical, and microbiological characteristics. The characteristic changes of ronto stored at low tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The total log number of mold decreased from 7.41 log CFU/g (day 0) to 7.12 log CFU/g (day 14). Other study using cincalok (small shrimp fermented product from West Kalimantan) reported similar result with the highest total mold reached log 6.0-7.2 CFU/g (Khairina et al 2016). During the joruk fermentation, mold is another microorganism that grow besides LAB.…”
Section: Total Moldmentioning
confidence: 61%
See 2 more Smart Citations
“…The total log number of mold decreased from 7.41 log CFU/g (day 0) to 7.12 log CFU/g (day 14). Other study using cincalok (small shrimp fermented product from West Kalimantan) reported similar result with the highest total mold reached log 6.0-7.2 CFU/g (Khairina et al 2016). During the joruk fermentation, mold is another microorganism that grow besides LAB.…”
Section: Total Moldmentioning
confidence: 61%
“…On the 0 th day of the joruk fermentation, the TVB value was 23.29 mgN/100 g and it increased to 146.44 mgN/100 g on the 14 th day of fermentation. The TVB value for joruk which was stored for 14 days was higher than the TVB for cincalok which was stored for 14 days reaching 131.79 mgN/100 g (Novelia et al, 2020), but the TVB for joruk was lower than ronto (rebon shrimp fermented product from South Kalimantan) stored for 16 days which was 196.77 mg N/100 g (Khairina et al, 2016).…”
Section: Total Volatile Base (Tvb)mentioning
confidence: 99%
See 1 more Smart Citation